Gradient of Increasing Aurora B Kinase Activity Is Required for Cells to Execute Mitosis - Xu, Zhenjie (American Society for Biochemistry and Molecular Biology, 2010)
INCENP, Borealin, Survivin, and Aurora B kinase comprise the chromosomal passenger complex, an essential regulator of mitotic events. INCENP (inner centromere protein) binds and activates Aurora B through a feedback loop involving phosphorylation of a Thr-Ser-Ser (TSS) motif near the INCENP C terminus. Here, we have examined the role of the TSS motif in vertebrate cells using an DT40 INCENP(ON/OFF) conditional knock-out cell line in which mutants are expressed in the absence of wild-type INCENP. Our analysis confirms that regulated phosphorylation of the two serine residues (presumably by Aurora B) is critical for full activation of the kinase and is essential for cell viability. Cells expressing INCENP mutants bearing either phospho-null (TAA) or phospho-mimetic (TEE) mutations exhibit significant levels of Aurora B kinase activity but fail to undergo normal spindle elongation or complete cytokinesis. This work confirms previous suggestions that INCENP can act as a rheostat, with different INCENP mutants promoting differing degrees of kinase activation. Our results also reveal that mitotic progression is accompanied by a requirement for progressively higher levels of Aurora B kinase activity.